Ultrastructural changes of optic analyzer elements after intracranial part of optic nerve traumatic injury in experiment - V. I. Tsymbaliuk; A. T. Nosov; Yu. V. Tsymbaliuk; V. V. Vaslovich; V. V. Medvedev (Ukrainian Neurosurgical Journal, 2010)
Experimental research data about rabbit’s optic nerve ultrastructure on different levels in remote period after left optic nerve cutting are generalized. In remote periods of research in all links of optic analyzer destructive-degenerative and reactive-reparative changes were observed. Disorders of neurons’ synaptic apparatus did not disappear in remote period, and showed themselves as plastic rebuilding, and their morphological criteria, in particular — perforated contact areas presence.